The Proliferation of False Reporting and the Fabrication of Charges in Post-Occupation - Maan Zaki Kadhim Al Karraawi; Rasem Mseer Jasim (International Journal of Law Research and Studies, 2026)
One of the critical negative phenomena plaguing contemporary societies is the offense of false reporting. Its detrimental impact is not merely confined to the perpetrator and the victim; rather, it extends to the broader community, undermining its social, moral, and religious foundations. This phenomenon has notably proliferated following the 2003 occupation of Iraq. This escalation has prompted the researcher to address this hazardous issue by examining the conceptual framework of the crime of false reporting, its legal significance, and its distinction from other analogous legal concepts. Furthermore, this study delineates the requisite criminal intent and the rationale underlying its criminalization. The researcher also analyzes the legal characterization (qualification) of the offense, its constituent elements, and its various forms and motives. Ultimately, the study concludes with a final section presenting key findings and practical recommendations.
Keywords: False Reporting; Fabrication of Charges; Occupation; Iraq